2009
DOI: 10.1007/s11357-009-9109-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation in mice exhibits genetic variability early in senescence

Abstract: Aging leads to a loss of thermoregulation that can be readily monitored in laboratory mice. However, it is unclear from previous studies-we provide a tabular summary of 15 articles-whether significant loss occurs by midlife (∼15 months of age). In this study, we examined 34 females from 22 LSXSS strains starting at 4 and 8 months of age (17 mice per age group). We used transponders inserted just under the loose skin of the pelt and calibrated against rectal body temperature to measure temperatures quickly with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This response is believed to be under genetic control and to have evolved as a mechanism to save energy, prolonging survival until more food becomes available [8,9]. The molecules and the signals that are involved in regulating this physiological adaptation are beginning to be identified [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This response is believed to be under genetic control and to have evolved as a mechanism to save energy, prolonging survival until more food becomes available [8,9]. The molecules and the signals that are involved in regulating this physiological adaptation are beginning to be identified [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, data on mice are highly inconsistent which might be due, for example, to different amount of handling stress when animals are restrained for temperature assessment. Nevertheless, a study using sensors inserted under the loose skin of the pelt of mice was able to show a drop in body temperature with aging [79].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly people have altered responses to changes in body temperature and are unable to regulate their body temperatures as efficiently as young adults (Güneş and Zaybak, 2008). Several studies reported that body temperature generally decrease in older people (DeGroot and Kenney, 2007;Güneş and Zaybak, 2008;Lu et al, 2009), and a similar pattern has also been shown in various animal models, such as laboratory mice and rats (Balmagiya and Rozovski, 1983;Talan and Engel, 1986;Scarpace et al, 1994;Gonzales and Rikke, 2010). The decreased body temperature in aged individuals can at least be partly due to the age-related decline of the basal metabolic rate (BMR) (review in De Magalhães et al, 2007;Moe et al, 2009) and a decreased thermogenic capacity (Lin et al, 2015).…”
Section: Introductionmentioning
confidence: 94%